Prediction of electrical conductivity, double percolation limit and electromagnetic interference shielding effectiveness of copper nanowire filled flexible polymer blend nanocomposites. (1st May 2019) - Ravindren, Revathy; Mondal, Subhadip; Nath, Krishnendu; Das, Narayan Ch
Abstract: Polymer nanocomposite containing metal nanowires are of an advanced class of conductive material. Here, we employed copper nanowire as a conductive filler in highly flexible EMA/EOC (50/50 wt%) binary blend to fabricate highly conductive, lightweight and flexible conductive polymer composite via solution mixing technique. The newly developed composite gave double percolation conductive network by selective localization of the nanowire in one of the binary phase. High conductivity in the range 10 2  S/cm was attained beyond percolation which was more than that achieved with most of the carbonaceous filler. This composite finds potential application as EMI shielding material for modern electronic devices and was demonstrated in this study. Absorption driven shielding efficiency of −45 dB was attained with 15 wt % copper nanowire loading. Graphical abstract: Image 1